Compact single-stage input-powered bridge rectifier with boost switch with high output power for energy harvesting system using 0.18-micron CMOS technology / Roskhatijah Radzuan - Radzuan, Roskhatijah (Institute of Graduate Studies, UiTM, 2017)
The demand on microwatt to milliwatts energy harvesting systems has been increasing recently with the increase of the needs for wireless self-powered device applications. With the small output voltage and the AC output from the micro harvesting generators, highly precise specifications, leading to challenging designs, optimizations and realizations of its every component are imposed. Rectifier, which is normally located right after the energy generator in the energy harvesting system, is required to be compact, with high efficiency to produce as high output power as possible. It is in this context that this thesis is focusing, where a new topology of CMOS bridge rectifier is proposed, offering advantages in terms of the compactness and high output power, which is suitable for wireless power devices applications. CMOS technology is seen as a straightforward solution for compactness as it offers possibility to reduce the full wave rectifier circuit size. The proposed rectifier circuit topology is designed such that the threshold voltage, which is a common source of voltage drop in the system, can be reduced, in order to maintain high output voltage…